Isolation and characterization of two phages against emetic Bacillus cereus and their potential applications - Bo Chen; Zhichao Huang; Xiaoming Yuan; Chun Li; Juan Wang; Moutong Chen; Liang Xue; Jumei Zhang; Qingping Wu; Yu Ding (Food Frontiers)
Abstract Bacillus cereus is a common foodborne pathogen capable of producing cereulide and enterotoxin. Consumption of food contaminated with cereulide can even result in fatality. Bacteriophages are increasingly being utilized as biocontrol agents to combat specific pathogens in a variety of food products. However, there are currently no lytic phages available to target cereulide‐producing B. cereus. This study aims to isolate and characterize two novel phages, DC1 and DC2, and assess their potential for use in food substrates. These two phages possessed the widest host range among the reported lytic phages that target B. cereus. The whole genome analysis demonstrated that DC1 and DC2 belonged to the Tsarbombavirus genus of the Bastillevirinae subfamily, which is part of the Herelleviridae family. The one‐step growth curve analysis revealed that DC1 had a latent period of 30 min and a burst size of approximately 39 PFU (plaque‐forming units) per cell. On the other hand, DC2 exhibited a shorter latent period of 15 min and a larger burst size of 124 PFU per cell. Both phages had a burst period of 30 min. Furthermore, DC1 and DC2 displayed excellent stability within a wide range of pH levels and temperatures. After undergoing a brief phage‐soaking treatment, DC1 and DC2 effectively reduced the bacterial count in spiked food samples. Additionally, they inhibited the formation of biofilms and degraded already‐formed biofilms. Collectively, DC1 and DC2 exhibit great potential as biocontrol agents for the prevention and control of B. cereus contamination in foods.